2020
DOI: 10.1097/md.0000000000023096
|View full text |Cite
|
Sign up to set email alerts
|

Flipped classroom combined with human anatomy web-based learning system shows promising effects in anatomy education

Abstract: Flipped classroom has received much attention in medical education. The aim of this study was to evaluate the efficacy of flipped classroom combing with human anatomy web-based learning system in anatomy education. A total of 89 freshmen in medical specialty were enrolled and randomly allocated into either the experimental group (receiving the flipped classroom with human anatomy web-based learning system, n = 45) or control group (receiving the traditional classroom teaching, n = 44). A pre-quiz an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 23 publications
5
36
0
4
Order By: Relevance
“…Feedback by students clearly summarized that they liked this new method of learning. Findings were consistent with previous studies that the FC method fostered students’ abilities in analyzing and solving clinical problems, thus improving the higher level of cognitive abilities [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Feedback by students clearly summarized that they liked this new method of learning. Findings were consistent with previous studies that the FC method fostered students’ abilities in analyzing and solving clinical problems, thus improving the higher level of cognitive abilities [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…For this we infer shorter videos are more suitable for students who are internships in hospitals because of their tight time and more conducive for them to integrate materials into the background of the entire course. As for offline courses, most interns said that they liked the form of teacher-student interaction, and the previous article also reached a similar conclusion [ 25 ]. Although most interns thought that they could accept the FC, the students who had just come into contact with it needed a certain period of adaption, during which they could be familiar with and accept it [ 29 ].…”
Section: Discussionmentioning
confidence: 77%
“…In the FC questionnaires, most interns thought that online courses were a good way to prepare before class, and previous studies had similar conclusion [ 12 ]. A study showed that the FC model increased their interest in learning because it allowed students to think independently and find answers through grouping, a process that stimulates learning motivation [ 25 ]. Analyzing the reasons why pre-recorded videos increase the enthusiasm for learning, researches has shown that they enable students to arrange their study plants at their own place, regardless of time and place.…”
Section: Discussionmentioning
confidence: 99%
“…Atividades em grupo (exercícios, debates, fóruns de discussão e outros). Oliveira et al, 2018;Melo Júnior et al, 2018;Menegaz et al, 2018;Andrés, 2018;Domínguez et al, 2015;Tang et al, 2017;Hsu et al, 2016;El-Banna et al, 2017;Ihm et al, 2017;Nishigawa et al, 2017;Lossius et al, 2016;Mc Lean et al, 2016;Gopalan & klann, 2017;Fátima et al, 2017;Kim et al, 2018;Xião et al, 2018;Jung, 2018;Kohli et al, 2019;Cho & Kim, 2019;Roe et al, 2019;Borit & Stangbaltaite-Mouhat, 2020;Halasa et al, 2020;Zheng & Zhang, 2020;Zheng et al, 2019;Shah et al, 2020;Yang et al, 2020;Sajid et al, 2016. Materiais de leitura / atividades assíncronas antes do encontro síncrono (online) ou presencial em sala de aula (artigos, livros e outros) Oliveira et al, 2018;Melo Júnior et al, 2018;Menegaz et al, 2018;Andrés 2018;Domínguez et al, 2015;Tang et al, 2017;Jesurasa et al, 2017;Rui et al, 2017;Cheng et al, 2016;Green & Schlairet, 2017;Ridell et al, 2016;King et al, 2017;Lee & Kim, 2018;Cho & Kim, 2019;Graham et al, 2019;…”
Section: Estudosunclassified
“…Atividades de avaliação de conhecimentos (questionários, pré e pós-testes, formulários avaliativos, perguntas e respostas, feedback e outros) Lucardie et al, 2017;Bonnes et al, 2017;Carrick et al, 2017;Lin et al, 2017;Lew, 2016;Sajid et al, 2016;Lochner et al, 2016;Mc Lean et al, 2016;Wu et al, 2018;Beom et al, 2018;Lee & Kim, 2018;Sohn et al, 2019;Kohler et al, 2020;Wu et al, 2020;Zante et al, 2020. Materiais audiovisuais (figuras, gráficos visuais, mapas mentais/conceituais, materiais de áudio, podcasts, palestras previamente gravadas e outros) Fleagle et al, 2018;Fátima, et al, 2017;Herrero et al, 2020;Bossaer et al, 2016;Boysen-Osborn et al, 2016;Petit et al, 2017;Kurup et al, 2020;Wu et al, 2020;Yang et al, 2020;Ferrer-Torregrosa et al, 2016;Lin et al, 2017. Aulas expositivas através de slides (aulas tradicionais) Hsu et al, 2016;Boysen-Osborn et al, 2016;Mc Lean et al, 2016;Petit et al, 2017;Beom et al, 2018;Yang et al, 2020.…”
Section: Estudosunclassified